Evaluating protected areas’ coverage of threats to terrestrial biodiversity - Pulido‐Chadid, Katherine; Rahbek, Carsten; Geldmann, Jonas (Conservation biology, 2025)
Protected areas (PAs) are vital for biodiversity conservation and have expanded globally. However, increasing pressures on biodiversity make it difficult to achieve conservation goals. Using threat probability maps based on the International Union for Conservation of Nature Red List and the World Database of Protected Areas, we analyzed the relationship between PA coverage and the major threats to amphibians, birds, mammals, and reptiles—agriculture, hunting, logging, pollution, invasive species, and urbanization. We included data on 33,379 species and 255,848 protected sites. We analyzed the relationship between threat probabilities and PA coverage with generalized additive models. Then, we grouped grid cells into discrete threat‐protection categories and examined global spatial patterns. We focused three types of areas: areas with a high probability of threat that coincided with inadequate PA coverage; areas that had simultaneous threats; and areas with a high concentration of threatened species. We found a potential disconnect between global PAs and threat coverage. Twenty‐one percent of areas had a high probability of threat, of which 76% were insufficiently protected. Over half of amphibian and mammal habitat was highly threatened and was insufficiently covered by PAs. Amphibians were subject to the highest proportion of simultaneous threats. Underprotected areas harbored the largest proportion of threatened species across all taxonomic groups. Our results provide crucial insights into the spatial relationship between threats and PA coverage and can be used to inform conservation planning at large scales. 【摘要】 保护地对生物多样性保护至关重要, 并已在全球范围内不断扩张。然而, 生物多样性面临的压力越来越大, 导致保护目标难以实现。本研究利用基于《国际自然保护联盟红色名录》和世界保护地数据库的威胁概率图, 分析了保护地覆盖情况与两栖动物、鸟类、哺乳动物和爬行动物面临的主要威胁(即农业、狩猎、伐木、污染、入侵物种和城市化)之间的关系。研究包含来自33,379个物种和255,848个保护地的数据。我们利用广义加性模型分析了威胁概率与保护区覆盖之间的关系, 并将网格单元划分为离散的威胁‐保护类别, 以分析其全球空间格局。我们聚焦于受威胁概率高、保护地覆盖不足、同时存在威胁和受威胁物种高度集中的区域。结果显示, 全球保护地与威胁覆盖区域之间可能存在脱节。21%的区域有较高的威胁概率, 而其中76%的区域没有得到充分保护。超过一半的两栖动物和哺乳动物栖息地受到高度威胁, 同时得到的保护地覆盖不足。两栖动物存在同时威胁的比例最高。在所有类群分组中, 栖息在保护不足地区的受威胁物种比例最高。以上研究结果为了解威胁与保护地覆盖之间的空间关系提供了重要见解, 可为大尺度的保护规划提供信息。 【翻译:胡怡思;审校:聂永刚】